2022
DOI: 10.1101/2022.11.10.515924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermal phenotypic plasticity of pre- and post-copulatory male harm buffers sexual conflict in wildDrosophila melanogaster

Abstract: Strong sexual selection frequently leads to sexual conflict and ensuing male harm, whereby males increase their reproductive success at the expense of harming females. Male harm is a widespread evolutionary phenomenon with a strong bearing on population viability. Thus, understanding how it unfolds in the wild is a current priority. Here, we sampled a wild Drosophila melanogaster population and studied male harm across the normal range of temperatures under which it reproduces optimally in nature by comparing … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…We predicted that this negative demographic impact can be mitigated by environmental complexity and increased opportunities for individuals to modulate behaviour in response to the intensity of mating interactions and that this effect would become more apparent and of greater importance during rapid environmental change and population decline (Londoño‐Nieto et al., 2022; Martínez‐Ruiz & Knell, 2017; Svensson & Connallon, 2019). We found evidence for this prediction, with N + S populations derived from sexually selected experimental evolution lines maintaining higher census sizes (Figure 2) and more stable growth rates (Figure 3) when reared in complex environments under the heatwave, compared to N population derived from monogamous lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We predicted that this negative demographic impact can be mitigated by environmental complexity and increased opportunities for individuals to modulate behaviour in response to the intensity of mating interactions and that this effect would become more apparent and of greater importance during rapid environmental change and population decline (Londoño‐Nieto et al., 2022; Martínez‐Ruiz & Knell, 2017; Svensson & Connallon, 2019). We found evidence for this prediction, with N + S populations derived from sexually selected experimental evolution lines maintaining higher census sizes (Figure 2) and more stable growth rates (Figure 3) when reared in complex environments under the heatwave, compared to N population derived from monogamous lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theoretical studies have shown that this type of sexual conflict could lead to increased extinction risk in already maladapted populations (Flintham et al., 2023; Gómez‐Llano et al., 2023; Martínez‐Ruiz & Knell, 2017). Moreover, as males of high genetic quality are likely to impose more harm to their female mates compared to males of low quality (Baur et al., 2022; Londoño‐Nieto et al., 2022; Yun et al., 2017), this effect could cancel out or even outweigh any potential population benefits of purifying sexual selection on male genetic quality (Chenoweth et al., 2015; Flintham et al., 2023).…”
Section: Introductionmentioning
confidence: 99%